Chitin-Induced Airway Epithelial Cell Innate Immune Responses Are Inhibited by Carvacrol/Thymol - Khosravi, Ali Reza (PLoS One, 2016)
Chitin is produced in large amounts by fungi, insects, and other organisms and has been implicated in the pathogenesis of asthma. Airway epithelial cells are in direct contact with environmental particles and serve as the first line of defense against inhaled allergens and pathogens. The potential contributions of airway epithelial cells to chitin-induced asthma remain poorly understood. We hypothesized that chitin directly stimulates airway epithelial cells to release cytokines that promote type 2 immune responses and to induce expression of molecules which are important in innate immune responses. We found that chitin exposure rapidly induced the expression of three key type 2-promoting cytokines, IL-25, IL-33 and TSLP, in BEAS-2B transformed human bronchial epithelial cells and in A549 and H292 lung carcinoma cells. Chitin also induced the expression of the key pattern recognition receptors TLR2 and TLR4. Chitin induced the expression of miR-155, miR-146a and miR-21, each of which is known to up-regulate the expression of pro-inflammatory cytokines. Also the expression of SOCS1 and SHIP1 which are known targets of miR-155 was repressed by chitin treatment. The monoterpene phenol carvacrol (Car) and its isomer thymol (Thy) are found in herbal essential oils and have been shown to inhibit allergic inflammation in asthma models. We found that Car/Thy inhibited the effects of chitin on type 2-promoting cytokine release and on the expression of TLRs, SOCS1, SHIP1, and miRNAs. Car/Thy could also efficiently reduce the protein levels of TLR4, inhibit the increase in TLR2 protein levels in chitin plus Car/Thy-treated cells and increase the protein levels of SHIP1 and SOCS1, which are negative regulators of TLR-mediated inflammatory responses. We conclude that direct effects of chitin on airway epithelial cells are likely to contribute to allergic airway diseases like asthma, and that Car/Thy directly inhibits epithelial cell pro-inflammatory responses to chitin.